The cultural codes transmitted to the audience through animated films in Soviet Kyrgyz cinema - Erdoğan Çakar Banu (SHS Web of Conferences)
The primary objective of this study is to identify the animated films produced in Kyrgyz cinema during the Soviet Union era and to reveal the cultural values transmitted to children through these films. The population of the study consists of animated films produced in Kyrgyz cinema during the Soviet period. It was determined that 30 films were produced between 1978 and 1991. Using a purposive sampling method, 13 films were selected as the sample of the study, with each film representing a different year. The study employed semiotic analysis and qualitative content analysis methods. The analysis revealed that visual codes in the films include Kyrgyz national clothing, the “boz-üy” (the traditional Kyrgyz yurt), national motifs used in living spaces, and traditional musical instruments as symbols. It was found that the animated films produced in Kyrgyz cinema during the Soviet period conveyed significant social and cultural values related to both Soviet ideology and Kyrgyz national culture. When the values presented in the animated films were compared with UNESCO’s universal values, the value of responsibility appeared most frequently, while no storyline corresponding to the values of honesty or simplicity was identified.